Effect of TiC-CNT precipitates on the microstructure and hardness of coatings welded by the GTAW process - Fabíola Pantoja Pinheiro, Paula; Ricardo Loayza Loayza, Cristhian; Gedael Fagundes Júnior, José [UNESP]; Patrícia Aranha da Paz, Simone; de Magalhães Braga, Eduardo; Allan Leite dos Reis, Marcos (Elsevier, 2024)
Carbon nanotubes (CNT)-reinforced metal matrix nanocomposites balance toughness and ductility and, therefore, can reduce maintenance costs of industrial equipment. In this sense, flux-cored made of low carbon steel filled with CNT/Ti6Al4V/CaF2 were used as filler metal to coat an A131 grade A steel sheet via GTAW process. SEM and Raman spectroscopy analyses evidence the partial phase transformation between Ti and CNT in TiC-CNT precipitates, which can act as barriers to dislocation movements in a ferritic matrix. Consequently, the hardnesses of the coatings were up to 33.9–77.4 % higher than the base metal. Therefore, incorporating TiC-CNT precipitate-based reinforcements via arc welding can improve the hardness of conventional steels.
Keywords: Hardness; Microstructure; Nanocomposite; Reinforcement; Welding